The assessment of antidiabetic properties of novel synthetic curcumin analogues: α-amylase and α-glucosidase as the target enzymes - Hasaninezhad, Fatemeh (J Diabetes Metab Disord, 2020)
Diabetes mellitus is a metabolic disorder characterized by high blood glucose levels and instability in carbohydrate metabolism. For treating diabetes, one important therapeutic approach is reducing the postprandial hyperglycemia which can be managed by delaying the absorption of glucose through inhibition of the carbohydrate-hydrolyzing enzymes, α-amylase (α-Amy) and α-glucosidase (α-Gls) in the digestive tract. In this work, a new class of curcumin derivatives incorporating pyrano[2,3-d]pyrimidine heterocycles was synthesized using a multicomponent reaction between curcumin, aldehydes, and barbituric acid. Using UV-Vis spectroscopic method, the synthetic compounds were assessed for their inhibitory properties against α-Amy and α-Gls enzymes. Also, the antioxidant potential of these compounds was measured spectroscopically and compared with Trolox which is known as a gold standard to measure antioxidant capacity. The results of present study suggest that the curcumin derivatives were able to efficiently inhibit both yeast and mammalian α-Gls. In comparison with the antidiabetic medicine acarbose, the synthetic curcumin derivatives were also capable to inhibit more effectively the yeast α-Gls. The partial inhibitory effects of these compounds against pancreatic α-Amy were also important in the terms of avoiding development of the possible gastrointestinal side effects. Moreover, some of the curcumin derivatives indicated stronger antioxidant activity than Trolox. Overall, these synthetic curcumin analogues might be considered as novel molecular templates for development of efficient antidiabetic compounds with promising inhibitory activities against α-Amy and α-Gls enzymes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40200-020-00685-z.